2021
DOI: 10.48550/arxiv.2101.03479
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Revisiting the Aretakis constants and instability in two-dimensional Anti-de Sitter spacetimes

Takuya Katagiri,
Masashi Kimura

Abstract: We discuss dynamics of massive Klein-Gordon fields in two-dimensional Anti-de Sitter spacetimes (AdS 2 ), in particular conserved quantities and non-modal instability on the future Poincaré horizon called, respectively, the Aretakis constants and the Aretakis instability. We find out the geometrical meaning of the Aretakis constants and instability in a parallel-transported frame along a null geodesic, i.e., some components of the higher-order covariant derivatives of the field in the paralleltransported frame… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…We shall explicitly show that the Aretakis constants and instability correspond to, respectively, constants and blowups of some components of higher-order covariant derivatives of the field at late times in that frame along the horizons. This shows that a similar geometrical interpretation as in the AdS 2 case [30] is possible for our present setup.…”
Section: Aretakis Constants and Instability In The Parallelly Propaga...supporting
confidence: 80%
See 4 more Smart Citations
“…We shall explicitly show that the Aretakis constants and instability correspond to, respectively, constants and blowups of some components of higher-order covariant derivatives of the field at late times in that frame along the horizons. This shows that a similar geometrical interpretation as in the AdS 2 case [30] is possible for our present setup.…”
Section: Aretakis Constants and Instability In The Parallelly Propaga...supporting
confidence: 80%
“…In [19,22,[35][36][37], it has been shown that there exists one-to-one correspondence of the Aretakis constants and the Newman-Penrose constants [38] in four-dimensional extremal Reissner-Nordström black 1 It has been argued that in [19] the Aretakis instability in global AdS 2 is just a coordinate effect, while in [29] the Aretakis instability in the near-horizon geometry of extremal black holes is not the coordinate effect. In [30], contrary to the claim in [19], it has been shown that the late-time divergent behavior in global AdS 2 has a geometrical meaning: blowups of some component of covariant derivatives of fields in the parallelly propagated null geodesic frame.…”
mentioning
confidence: 84%
See 3 more Smart Citations